Nuclear and radiation physics in medicine : a conceptual introduction - Key, Tony (World Scientific, 2014)
An introduction to medical physics covering applications of modern physics, radiation, atomic and nuclear physics in medical diagnosis and cancer treatment. Presents fundamental principles of diagnosis and radiation therapy using basic physics and mathematics with practical exercises.